Am I a robot? English language teachers on teachers’ guides - Kiai, Alice Wanjira (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Teachers’ Guides were part of a wider textbook study that I carried out in Kenya (2008-2012), where both Students’ and Teachers’ Books undergo vetting for Ministerial approval. While this endorsement is important, there is, equally, a need to explore the responses to materials from the perspective of the end-users of the product. The aim of this article is to examine teachers’ views on Teachers’ Guides for secondary school English in Kenya, where English is a Second Language. Faceto-face teacher interviews (2010) provided more nuanced data than a preliminary survey questionnaire (2009), indicating rare or selective use of guidebooks for various reasons. Teacher insights into guidebooks are potentially useful to other teachers, teacher trainers, materials developers and regulatory bodies.